2021
DOI: 10.1177/1524838020985571
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Trauma and Violence Informed Care in Primary Health Care Settings for First Nations Women Experiencing Violence: A Systematic Review

Abstract: It is imperative that access to primary health care services is equitable as health care practitioners are often the first responders to women who experience violence. This is of particular importance for First Nations women who disproportionately experience interpersonal and structural violence when compared to non-First Nations women, as well as the ongoing impact of colonization, racism, and intergenerational trauma. To understand how primary health care services can provide equitable and effective care for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Diagnosis of a mental health condition was more frequently associated with the low prevalence disorder of schizophrenia. Workforce hesitancy in engaging and screening patients about their experiences of distress is a likely contributor to this result [28,29]. Improving workforce education and ensuring the availability of appropriate screening tools would likely see an increase in the numbers of patients diagnosed with common mental health disorders, such as depression and stress [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of a mental health condition was more frequently associated with the low prevalence disorder of schizophrenia. Workforce hesitancy in engaging and screening patients about their experiences of distress is a likely contributor to this result [28,29]. Improving workforce education and ensuring the availability of appropriate screening tools would likely see an increase in the numbers of patients diagnosed with common mental health disorders, such as depression and stress [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For responses to be effective with Indigenous women, significant systems change is required, as there is considerable evidence that demonstrates racism within the health system 75 . Support for health professionals to effectively respond requires both cultural safety and antiracism training, and inclusion of Indigenous women’s voices and needs to be tailored to context 76 . These are framed by the Australian Human Rights Commission’s recent report, Wiyi Yani U Thangani (Women’s Voices): securing our rights, securing our future , which has developed a framework for substantial system reform related to Indigenous women’s voice, representation and participation across a number of domains.…”
Section: System Supportmentioning
confidence: 99%
“…A survey of health clinics across Europe found several factors were key to making gender‐based violence work sustainable: committed leadership, regular training (with mandatory attendance) of staff from front‐desk workers to health practitioners, use of the trainer model with on‐site trainers, and a clear referral pathway 77 Box 4. brings together these guidelines, 15 factors, 77 and Indigenous women’s requirements 76 to represent a trauma‐ and violence‐informed system approach that is gender‐responsive, culturally safe and contextually tailored.…”
Section: System Supportmentioning
confidence: 99%
“…In fact, regardless of age or gender (e.g., she/he/they) [78], anyone could experience sexual assault and accompanying physical attacks and/or digital threats [84]. Moreover, the aftermath of sexual assault can be unimaginably painful [17,44,81]; survivors often experience severe physical and/or psychological trauma [16,44], sufer from anxiety of potential retaliation [33,54,83], and even self-harm or commit suicide [17,60,81]. In this vein, the WHO reported that sexual violence is a serious problem that negatively afects public health and violates human rights [90] and needs carefully designed humanitarian intervention.…”
Section: Introductionmentioning
confidence: 99%